0
$\begingroup$

Stuck on trying to find the Laurent series for $$\frac{e^z -1}{z^2}$$ centered at $z_0 = 0$. Still new to Laurent series, so not entirely sure how to get it. I know the Taylor series for $e^z$ but don't know how to deal with the -1 like that.

Any guidance would be very helpful

$\endgroup$
  • 1
    $\begingroup$ What is the first term of the Taylor series for $e^z$? $\endgroup$ – Zircht Apr 24 at 21:42
2
$\begingroup$

So you know the series for $e^z$. Which is to say, you're familiar with $$ e^z = 1 + z + \frac{z^2}2 + \frac{z^3}6 + \frac{z^4}{24} + \cdots $$ Now, subtracting $1$ means just that: subtract $1$. It's as easy as can be. $$ e^z - 1 = 1 + z + \frac{z^2}2 + \frac{z^3}6 + \frac{z^4}{24} + \cdots - 1\\ = z + \frac{z^2}2 + \frac{z^3}6 + \frac{z^4}{24} + \cdots $$ Finally, dividing by $z^2$ is similarly straight-forward: $$ \frac{e^z - 1}{z^2} = \frac{z + \frac{z^2}2 + \frac{z^3}6 + \frac{z^4}{24} + \cdots}{z^2}\\ = \frac1z + \frac12 + \frac z6 + \frac{z^2}{24} + \cdots $$

$\endgroup$
0
$\begingroup$

$e^z$ has Taylor series, about z= 0, $\sum_{n=0}^\infty \frac{z^n}{n!}= 1+ z+ \frac{z^2}{2}+ \frac{z^3}{3!}+ \cdot\cdot\cdot$. So $e^z- 1$ has series $\sum_{n=1}^\infty \frac{z^n}{n!}= z+ \frac{z^2}{2}+ \frac{z^3}{3!}+ \cdot\cdot\cdot$. Then $\frac{e^z-1}{z^2}=\frac{1}{z}+ \frac{1}{2}+ \frac{z}{3!}+ \cdot\cdot\cdot= \sum_{n=1}^\infty \frac{z^{n-2}}{n!}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.